JENIS DAN BANYAKNYA KAYU YANG DIPAKAI DALAM KONSTRUKSI JALAN REL DI HUTAN RAWA PROPINSI RIAU - Dulsalam Dulsalam; Apul Sianturi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1984)
An observation on the amount and species of wood used in rail-road construction in the swamp forests has been carried out in the PT Alam Wanasaki and PT Tenaga Kampar concession areas both located in Riau.The observation revealed that the wood species used in rail-road construction at the PT Alam Wanasaki area consist of 24 species with a volume of 243 m3/km. Those used at the PT Tenaga Kampar area consist of 12 species comprising a volume of 204 m3/km and the species used at the PT Alam Wanasaki area are mostly helat (Xylopia malayana Hooh .f.) with a total volume of 71 m3/km. The same is found at the PT Tenaga Kampar area using a total volume of 58 m3/km. Other wood species used in rail-road construction in both concession areas consist of a number of commercial species.Wood species which are considered suitable in the construction of rail-road in the swamp forests of PT Alam Wanasaki are among others: bintangur (Callophyllum .spp.), gelam (Eugenia spp.), medang (Litsea spp.), menggeris (Koompassia spp.), pelawan (Tristania obovata R.Br.), punak (Tetramerista glabra Miq.), resak (Cotylelobium melanoxylon Pierre.), tempurung (Baccaurea spp.), and tembesu (Fagraea spp.), comprising about 16% of the total volume used in the construction.Wood species selected for rail-road construction at the PT Tenaga Kampar concession area are: bintangur (Callophyllum spp.), medang (Litsea spp.), and punak (Tetramerista glabra Miq.), comprising 32% of the total amount of wood used in the construction.Both companies made efforts to onlv use durable wood species, however, such species are scarce.